Epidemiologia molecular das infecções por adenovírus em crianças com gastrenterite aguda grave, após a introdução da vacina contra rotavírus na cidade de Belém, Pará - MÜLLER, Elza Caroline Alves (Universidade Federal do Pará, 2017)
Gastroenteritis are the third cause of infant morbidity and mortality worldwide, especially among children under 5 years old. Adenoviruses (HAdV) are icosahedral non-enveloped viruses, possess 240 proteins "hexon" specific and a double-stranded DNA. They belong to the Adenoviridae family, Mastadenovirus genus, and are assigned to 7 species (A to G) and 57 serotypes. Epidemiological studies found that HAdVs account for 2-14% of cases of acute childhood diarrhea in hospitals and outpatient units. The aim of this study was to determine the prevalence and to assess the epidemiological features of of HAdV infection, as well as the occurrence of types in 842 children under three years of age, hospitalized for acute gastroenteritis in Belém, Brazil. All of these children had been vaccinated against rotavirus.These children were selected from a previous rotavirus vaccine case-control study conducted at Instituto Evandro Chagas, Belém, Pará, from May 2009 to April 2011. ELISA and immunochromatography were used for HAdV screening in stool samples and PCR and oligonucleotide sequencing for typing and molecular characterisation. HAdVs were found in 7.2% (61/842) of the tested samples, with the enteric adenoviruses (EAD) accounting for 50.8% (31/61) of the HAdV positive cases. The distribution of HAdV according to the gender showed that 7.7% (28/362) of whom were female and 6.8% (33/480) were male. The highest prevalence rates of HAdV infection were seen among patients older than 24 months of age, corresponding to 8.9% (16/178) of all positive cases. In regards to the temporal distribution, the highest prevalence rate was observed in June, representing 11.4% (8/70) of cases overall. The oligonucleotide sequencing showed that HAdV species F was predominant in our region, accounting for 64.5% (29/45) of the sequenced samples. These samples included HAdV types 41 and 40, detected at rates of 69% (20/29) cases and 31% (9/29), respectively. The results of this study indicate that HAdV accounts for a significant proportion of gastroenteritis among hospitalized children aged less than 3 years, during a post-rotavirus vaccine introduction period in Belém, Pará state, Brazil.